The role of demand in innovation: A lead market analysis for high-tech industries in the EU-25 - Thomas Cleff; Christoph Grimpe; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This document presents an indicator-based methodology that attempts to approximate the Lead Market attributes of EU-25 countries for four high-tech industries. A Lead Market is defined as a country where users prefer and demand a specific innovation design that not only appeals to domestic users, but can subsequently be commercialised successfully in other countries as well. A system of five particular country-specific attributes - the so called Lead Market factors - is regarded as critical for the probability of the market becoming a Lead Market. These factors, which influence a country's Lead Market potential, are as follows: price advantage, demand advantage, export advantage, transfer advantage and market structure advantage. The aim of this document is to identify and operationalise indicators to measure and compare the Lead Market properties at international level. The indicators used are taken from the Community Innovation Surveys (CIS-3 and CIS-4), the Eurostat/OECD PPP and Expenditure Database at BH level, the UNCTAD FDI-Database, the EU Business Demography Statistics, and the Eurostat Foreign Trade Database (Comext). Based on the Lead Market analysis, implications for policy makers are outlined.
urn:nbn:de:bsz:180-madoc-17682
Keywords: 650; Innovationsdiffusion; Nachfrage; Schlüsselsektor; Hochtechnologiesektor; Kraftfahrzeugindustrie; Chemieindustrie; Maschinenbau; IT-Industrie; EU-Staaten